TraCurate: Efficiently curating cell tracks - Sebastian Wagner; Konstantin Thierbach; Thomas Zerjatke; Ingmar Glauche; Ingo Roeder; Nico Scherf (SoftwareX, 2021)
TraCurate is an open-source software tool to curate and manually annotate cell tracking data from time-lapse microscopy. Although many studies of cellular behaviour require high-quality, long-term observations of single cells across several generations, automated tracking of individual cells is often imperfect and typically yields fragmented results that still contain many errors. TraCurate supports the user to efficiently curate and extract complete cell tracks and genealogies from a variety of cell tracking data. Source code and binary packages for TraCurate and all related tools are freely available for Linux, macOS, and Windows at https://tracurate.gitlab.io/.